Narrating the Green gods: the (auto) Biographies of Nigerian Military Rulers - Adeoti, Gbemisola (2014)
Since the inauguration of military rule through the first coup of Saturday, 15 January 1966, there has been no aspect of Nigerian life that has not experienced, whether positively or negatively, the reformative ardour of successive military regimes. As a result of the long span of military rule and the domination of political power by soldiers while military governance lasted, soldiers have had an immense impact on politics, education, sports, internal and international relations, economy, law, penology, resource allocation and so on. This observation has been made in diverse studies.